2015
DOI: 10.1634/theoncologist.2014-0475
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA in Digestive Tract Cancers: Function, Mechanism, and Potential Biomarker

Abstract: Digestive tract cancers (DTCs) are a leading cause of cancerrelated death worldwide. Current therapeutic tools for advanced stage DTCs have limitations, and patients with early stage DTCs frequently have a missed diagnosis due to shortage of efficient biomarkers. Consequently, it is necessary to develop novel biomarkers for early diagnosis and novel therapeutic targets for treatment of DTCs. In recent years, long noncoding RNAs (lncRNAs), a class of noncoding RNAs with .200 nucleotides, have been shown to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…lncRNAs are a major research focus, and their number exceeds that of protein-coding RNAs. An increasing number of lncRNAs that participate in gene regulation are being discovered (16). Ever since the discovery of HOTAIR, an important representative lncRNA, research has shown that it is abnormally expressed in many types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are a major research focus, and their number exceeds that of protein-coding RNAs. An increasing number of lncRNAs that participate in gene regulation are being discovered (16). Ever since the discovery of HOTAIR, an important representative lncRNA, research has shown that it is abnormally expressed in many types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…93 LncRNAs can be targeted therapeutically by a variety of approaches including (i) RNA interference (RNAi)-mediated downregulation of specific lncRNAs; (ii) antisense oligonucleotides (ASO)-based therapy; (iii) plasmid-based therapy; (iv) lncRNA mimics or small-molecule inhibitors; (v) gene therapy, and so on. 94 Although RNAi technology offers immense therapeutic promise due to its high potency, the main obstacle of siRNA/shRNA-based therapeutics remains its poor delivery in vivo . In contrast to RNAi, ASOs are synthetic, short, single-stranded DNAs or RNAs (between 8 and 50 nt), another type of nucleic acid drugs, which are designed with sequence specificity to target lncRNAs.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…It is well known that lncRNAs participate in cancer-associated pathways (7). Although an increasing number of lncRNAs have been reported to functionally regulate the metastatic behavior of GC cells, a large number of lncRNAs require identification, as 70-90% of the human genome transcribes RNA products, whereas protein-coding genes account for only 2% (8). Therefore, the present study focused on an lncRNA, AFAP1-antisense RNA 1 (AFAP1-AS1), which was first observed in esophageal cancer and acted as an oncogene, mediating effects in cell proliferation, migration and invasion (9).…”
Section: Introductionmentioning
confidence: 99%